Daytime systolic ambulatory blood pressure with a two-step switch from candesartan to olmesartan monotherapy and the fixed-dose combination of olmesartan/amlodipine in patients with uncontrolled essential hypertension (SEVICONTROL-2) - Bramlage, Peter; Zemmrich, Claudia; Gansz, Andrea; Sturm, Claus-Dieter; Fimmers, Rolf; Nadal, Jennifer; Schmieder, Roland; Schrader, Joachim; Lueders, Stephan (Journal of Clinical Hypertension, 2014)
The objective of this study was to investigate the efficacy of the fixed-dose combination olmesartan/amlodipine 40/10 mg in patients with moderate essential hypertension not controlled on candesartan 32 mg. This was a prospective, single-arm, phase IV study. The primary endpoint was the change in mean daytime systolic blood pressure (BP). A total of 77 of 89 screened patients started candesartan 32 mg, 62 olmesartan 40 mg, and 57 olmesartan 40 mg/amlodipine 10 mg. Mean daytime systolic BP was reduced by 9.8±15.2 mm Hg (P<.001) vs candesartan monotherapy. Office BP reduction was 9.2±18.8/5.0±8.9 mm Hg (P<0.001). Treatment goals (<140/90 mm Hg for office and <135/85 mm Hg for ambulatory BP) were achieved in 58.2% and 78.4% of patients, respectively. There was one drug-related adverse event (edema) and no serious adverse events. Patients of Caucasian ethnicity with moderate essential hypertension uncontrolled on candesartan experienced a further drop in BP using olmesartan and amlodipine.
EVALuna2:3682